Complementarity problem

From Wikimization

(Difference between revisions)
Jump to: navigation, search
(Remark)
Line 1: Line 1:
Sándor Zoltán Németh
Sándor Zoltán Németh
-
=== Fixed point problems ===
+
== Fixed point problems ==
Let <math>\mathcal A</math> be a set and <math>F:\mathcal A\to\mathcal A </math> a mapping. The '''fixed point problem''' defined by <math>F\,</math> is the problem
Let <math>\mathcal A</math> be a set and <math>F:\mathcal A\to\mathcal A </math> a mapping. The '''fixed point problem''' defined by <math>F\,</math> is the problem
Line 15: Line 15:
</center>
</center>
-
=== Nonlinear complementarity problems ===
+
== Nonlinear complementarity problems ==
Let <math>\mathcal K</math> be a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone] in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f:\mathbb H\to\mathbb H</math> a mapping. Recall that the dual cone of <math>\mathcal K</math> is the closed [http://en.wikipedia.org/wiki/Convex_cone convex cone] <math>\mathcal K^*=-\mathcal K^\circ,</math> where <math>\mathcal K^\circ</math> is the [[Moreau's_decomposition_theorem#Moreau.27s_theorem |polar]] of <math>\mathcal K.</math> The '''nonlinear complementarity problem''' defined by <math>\mathcal K</math> and <math>f\,</math> is the problem
Let <math>\mathcal K</math> be a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone] in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f:\mathbb H\to\mathbb H</math> a mapping. Recall that the dual cone of <math>\mathcal K</math> is the closed [http://en.wikipedia.org/wiki/Convex_cone convex cone] <math>\mathcal K^*=-\mathcal K^\circ,</math> where <math>\mathcal K^\circ</math> is the [[Moreau's_decomposition_theorem#Moreau.27s_theorem |polar]] of <math>\mathcal K.</math> The '''nonlinear complementarity problem''' defined by <math>\mathcal K</math> and <math>f\,</math> is the problem
Line 29: Line 29:
</center>
</center>
-
=== Every nonlinear complementarity problem is equivalent to a fixed point problem ===
+
== Every nonlinear complementarity problem is equivalent to a fixed point problem ==
Let <math>\mathcal K</math> be a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone] in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f:\mathbb H\to\mathbb H</math> a mapping. Then, the [[Complementarity_problem#Nonlinear_complementarity_problems | nonlinear complementarity problem]] <math>NCP(f,\mathcal K)</math> is equivalent to the [[Complementarity_problem#Fixed_point_problems | fixed point problem]]
Let <math>\mathcal K</math> be a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone] in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f:\mathbb H\to\mathbb H</math> a mapping. Then, the [[Complementarity_problem#Nonlinear_complementarity_problems | nonlinear complementarity problem]] <math>NCP(f,\mathcal K)</math> is equivalent to the [[Complementarity_problem#Fixed_point_problems | fixed point problem]]
<math>Fix(P_{\mathcal K}\circ(I-f)),</math> where <math>I:\mathbb H\to\mathbb H</math> is the identity mapping defined by <math>I(x)=x\,</math> and <math>P_{\mathcal K}</math> is the [[Moreau's_decomposition_theorem#Projection_on_closed_convex_sets | projection onto <math>\mathcal K.</math>]]
<math>Fix(P_{\mathcal K}\circ(I-f)),</math> where <math>I:\mathbb H\to\mathbb H</math> is the identity mapping defined by <math>I(x)=x\,</math> and <math>P_{\mathcal K}</math> is the [[Moreau's_decomposition_theorem#Projection_on_closed_convex_sets | projection onto <math>\mathcal K.</math>]]
-
=== Proof ===
+
== Proof ==
For all <math>x\in\mathbb H</math> denote <math>z=x-f(x)\,</math> and <math>y=-f(x).\,</math> Then, <math>z=x+y.\,</math>
For all <math>x\in\mathbb H</math> denote <math>z=x-f(x)\,</math> and <math>y=-f(x).\,</math> Then, <math>z=x+y.\,</math>
<br>
<br>
Line 51: Line 51:
<math>x\in\mathcal K,</math> <math>f(x)=-y\in\mathcal K^*</math> and <math>\langle x,f(x)\rangle=0.</math> Therefore, <math>x\,</math> is a solution of <math>NCP(f,\mathcal K).</math>
<math>x\in\mathcal K,</math> <math>f(x)=-y\in\mathcal K^*</math> and <math>\langle x,f(x)\rangle=0.</math> Therefore, <math>x\,</math> is a solution of <math>NCP(f,\mathcal K).</math>
 +
== An alternative proof without [[Moreau's_decomposition_theorem#Moreau.27s_theorem | Moreau's theorem]] ==
-
=== An alternative proof without [[Moreau's_decomposition_theorem#Moreau.27s_theorem | Moreau's theorem]] ===
+
=== Variational inequalities ===
-
==== Variational inequalities ====
+
Let <math>\mathcal C</math> be a closed convex set in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f:\mathbb H\to\mathbb H</math> a mapping. The '''variational inequality''' defined by <math>\mathcal C</math> and <math>f\,</math> is the problem
Let <math>\mathcal C</math> be a closed convex set in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f:\mathbb H\to\mathbb H</math> a mapping. The '''variational inequality''' defined by <math>\mathcal C</math> and <math>f\,</math> is the problem
Line 67: Line 67:
</center>
</center>
-
==== Every variational inequality is equivalent to a fixed point problem ====
+
=== Every variational inequality is equivalent to a fixed point problem ===
Let <math>\mathcal C</math> be a closed convex set in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f:\mathbb H\to\mathbb H</math> a mapping. Then the [[Complementarity_problem#Variational_inequalities | variational inequality]] <math>VI(f,\mathcal C)</math> is equivalent to the [[Complementarity_problem#Fixed_point_problems | fixed point problem]] <math>Fix(P_{\mathcal C}\circ(I-f)).</math>
Let <math>\mathcal C</math> be a closed convex set in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f:\mathbb H\to\mathbb H</math> a mapping. Then the [[Complementarity_problem#Variational_inequalities | variational inequality]] <math>VI(f,\mathcal C)</math> is equivalent to the [[Complementarity_problem#Fixed_point_problems | fixed point problem]] <math>Fix(P_{\mathcal C}\circ(I-f)).</math>
-
==== Proof ====
+
=== Proof ===
<math>x\,</math> is a solution of <math>Fix(P_{\mathcal C}\circ(I-f))</math> if and only if
<math>x\,</math> is a solution of <math>Fix(P_{\mathcal C}\circ(I-f))</math> if and only if
<math>x=P_{\mathcal C}(x-f(x)).</math> By using the [[Moreau's_decomposition_theorem#Characterization_of_the_projection | characterization of the projection]] the latter equation is equivalent to
<math>x=P_{\mathcal C}(x-f(x)).</math> By using the [[Moreau's_decomposition_theorem#Characterization_of_the_projection | characterization of the projection]] the latter equation is equivalent to
Line 81: Line 81:
of <math>VI(f,\mathcal C).</math>
of <math>VI(f,\mathcal C).</math>
-
===== Remark =====
+
=== Remark ===
The next section shows that the equivalence of [[Complementarity_problem#Variational_inequalities | variational inequalities]] and [[Complementarity_problem#Fixed_point_problems | fixed point problems]] is much stronger than the equivalence of [[Complementarity_problem#Nonlinear_complementarity_problems |nonlinear complementarity problems]] and [[Complementarity_problem#Fixed_point_problems | fixed point problems]], because each [[Complementarity_problem#Nonlinear_complementarity_problems |nonlinear complementarity problem]] is a [[Complementarity_problem#Variational_inequalities | variational inequality]] defined on a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone].
The next section shows that the equivalence of [[Complementarity_problem#Variational_inequalities | variational inequalities]] and [[Complementarity_problem#Fixed_point_problems | fixed point problems]] is much stronger than the equivalence of [[Complementarity_problem#Nonlinear_complementarity_problems |nonlinear complementarity problems]] and [[Complementarity_problem#Fixed_point_problems | fixed point problems]], because each [[Complementarity_problem#Nonlinear_complementarity_problems |nonlinear complementarity problem]] is a [[Complementarity_problem#Variational_inequalities | variational inequality]] defined on a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone].
-
==== Every variational inequality defined on a closed convex cone is equivalent to a complementarity problem ====
+
=== Every variational inequality defined on a closed convex cone is equivalent to a complementarity problem ===
Let <math>\mathcal K</math> be a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone] in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f:\mathbb H\to\mathbb H</math> a mapping. Then, the [[Complementarity_problem#Nonlinear_complementarity_problems | nonlinear complementarity problem]] <math>NCP(f,\mathcal K)</math> is equivalent to the [[Complementarity_problem#Variational_inequalities | variational inequality]] <math>VI(f,\mathcal K).</math>
Let <math>\mathcal K</math> be a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone] in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f:\mathbb H\to\mathbb H</math> a mapping. Then, the [[Complementarity_problem#Nonlinear_complementarity_problems | nonlinear complementarity problem]] <math>NCP(f,\mathcal K)</math> is equivalent to the [[Complementarity_problem#Variational_inequalities | variational inequality]] <math>VI(f,\mathcal K).</math>
-
==== Proof ====
+
=== Proof ===
Suppose that <math>x\,</math> is a solution of <math>NCP(f,\mathcal K).</math> Then, <math>x\in\mathcal K,</math> <math>f(x)\in\mathcal K^*</math> and <math>\langle x,f(x)\rangle=0.</math> Hence,
Suppose that <math>x\,</math> is a solution of <math>NCP(f,\mathcal K).</math> Then, <math>x\in\mathcal K,</math> <math>f(x)\in\mathcal K^*</math> and <math>\langle x,f(x)\rangle=0.</math> Hence,
Line 107: Line 107:
for all <math>y\in\mathcal K.</math> Particularly, taking <math>y=0\,</math> and <math>y=2x\,</math>, respectively, we get <math>\langle x,f(x)\rangle=0.</math> Thus, <math>\langle y,f(x)\rangle\geq 0,</math> for all <math>y\in\mathcal K,</math> or equivalently <math>f(x)\in\mathcal K^*.</math> In conclusion, <math>x\in\mathcal K,</math> <math>f(x)\in\mathcal K^*</math> and <math>\langle x,f(x)\rangle=0.</math> Therefore, <math>x\,</math> is a solution of <math>NCP(f,\mathcal K).</math>
for all <math>y\in\mathcal K.</math> Particularly, taking <math>y=0\,</math> and <math>y=2x\,</math>, respectively, we get <math>\langle x,f(x)\rangle=0.</math> Thus, <math>\langle y,f(x)\rangle\geq 0,</math> for all <math>y\in\mathcal K,</math> or equivalently <math>f(x)\in\mathcal K^*.</math> In conclusion, <math>x\in\mathcal K,</math> <math>f(x)\in\mathcal K^*</math> and <math>\langle x,f(x)\rangle=0.</math> Therefore, <math>x\,</math> is a solution of <math>NCP(f,\mathcal K).</math>
-
==== Concluding the alternative proof ====
+
=== Concluding the alternative proof ===
Since <math>\mathcal K</math> is a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone], the [[Complementarity_problem#Nonlinear_complementarity_problems | nonlinear complementarity problem]] <math>NCP(f,\mathcal K)</math> is equivalent to the [[Complementarity_problem#Variational_inequalities | variational inequality]] <math>VI(f,\mathcal K),</math> which is equivalent to the [[Complementarity_problem#Fixed_point_problems | fixed point problem]] <math>Fix(P_{\mathcal K}\circ(I-f)).</math>
Since <math>\mathcal K</math> is a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone], the [[Complementarity_problem#Nonlinear_complementarity_problems | nonlinear complementarity problem]] <math>NCP(f,\mathcal K)</math> is equivalent to the [[Complementarity_problem#Variational_inequalities | variational inequality]] <math>VI(f,\mathcal K),</math> which is equivalent to the [[Complementarity_problem#Fixed_point_problems | fixed point problem]] <math>Fix(P_{\mathcal K}\circ(I-f)).</math>
Line 127: Line 127:
</center>
</center>
-
=== Every implicit complementarity problem is equivalent to a fixed point problem ===
+
== Every implicit complementarity problem is equivalent to a fixed point problem ==
Let <math>\mathcal K</math> be a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone] in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f,g:\mathbb H\to\mathbb H</math> two mappings. Then, the [[Complementarity_problem#Implicit_complementarity_problems | implicit complementarity problem]] <math>ICP(f,g,\mathcal K)</math> is equivalent to the [[Complementarity_problem#Fixed_point_problems | fixed point problem]]
Let <math>\mathcal K</math> be a closed [http://en.wikipedia.org/wiki/Convex_cone convex cone] in the Hilbert space <math>(\mathbb H,\langle\cdot,\cdot\rangle)</math> and <math>f,g:\mathbb H\to\mathbb H</math> two mappings. Then, the [[Complementarity_problem#Implicit_complementarity_problems | implicit complementarity problem]] <math>ICP(f,g,\mathcal K)</math> is equivalent to the [[Complementarity_problem#Fixed_point_problems | fixed point problem]]
<math>Fix(I-g+P_{\mathcal K}\circ(g-f)),</math> where <math>I:\mathbb H\to\mathbb H</math> is the identity mapping defined by <math>I(x)=x.\,</math>
<math>Fix(I-g+P_{\mathcal K}\circ(g-f)),</math> where <math>I:\mathbb H\to\mathbb H</math> is the identity mapping defined by <math>I(x)=x.\,</math>
-
=== Proof ===
+
== Proof ==
For all <math>u\in\mathbb H</math> denote <math>z=g(u)-f(u),\,</math> <math>x=g(u)\,</math> and <math>y=-f(u).\,</math> Then,
For all <math>u\in\mathbb H</math> denote <math>z=g(u)-f(u),\,</math> <math>x=g(u)\,</math> and <math>y=-f(u).\,</math> Then,
<math>z=x+y.\,</math>
<math>z=x+y.\,</math>
Line 159: Line 159:
=== Remark ===
=== Remark ===
In particular if <math>g=I,</math> we obtain the result
In particular if <math>g=I,</math> we obtain the result
-
[[Moreau%27s_decomposition_theorem#Every_nonlinear_complementarity_problem_is_equivalent_to_a_fixed_point_problem | ''Every nonlinear complementarity problem is equivalent to a fixed point problem'']],
+
[[Complementarity_problem#Every_nonlinear_complementarity_problem_is_equivalent_to_a_fixed_point_problem | ''Every nonlinear complementarity problem is equivalent to a fixed point problem'']],
-
but the more general result [[Moreau%27s_decomposition_theorem#Every_implicit_complementarity_problem_is_equivalent_to_a_fixed_point_problem | ''Every implicit complementarity problem is equivalent to a fixed point problem'']] has no known connection with [[Complementarity_problem#Variational_inequalities | variational inequalities]]. Therefore, using [[Moreau's_decomposition_theorem#Moreau.27s_theorem | Moreau's theorem]] is essential for proving the latter result.
+
but the more general result [[Complementarity_problem#Every_implicit_complementarity_problem_is_equivalent_to_a_fixed_point_problem | ''Every implicit complementarity problem is equivalent to a fixed point problem'']] has no known connection with [[Complementarity_problem#Variational_inequalities | variational inequalities]]. Therefore, using [[Moreau's_decomposition_theorem#Moreau.27s_theorem | Moreau's theorem]] is essential for proving the latter result.

Revision as of 08:21, 20 July 2009

Sándor Zoltán Németh

Contents

Fixed point problems

Let LaTeX: \mathcal A be a set and LaTeX: F:\mathcal A\to\mathcal A a mapping. The fixed point problem defined by LaTeX: F\, is the problem

LaTeX: 
Fix(F):\left\{
\begin{array}{l}
Find\,\,\,x\in\mathcal A\,\,\,such\,\,\,that\\
F(x)=x.
\end{array}
\right.

Nonlinear complementarity problems

Let LaTeX: \mathcal K be a closed convex cone in the Hilbert space LaTeX: (\mathbb H,\langle\cdot,\cdot\rangle) and LaTeX: f:\mathbb H\to\mathbb H a mapping. Recall that the dual cone of LaTeX: \mathcal K is the closed convex cone LaTeX: \mathcal K^*=-\mathcal K^\circ, where LaTeX: \mathcal K^\circ is the polar of LaTeX: \mathcal K. The nonlinear complementarity problem defined by LaTeX: \mathcal K and LaTeX: f\, is the problem

LaTeX: 
NCP(f,\mathcal K):\left\{
\begin{array}{l} 
Find\,\,\,x\in\mathcal K\,\,\,such\,\,\,that\\ 
f(x)\in\mathcal K^*\,\,\,and\,\,\,\langle x,f(x)\rangle=0.
\end{array}
\right.

Every nonlinear complementarity problem is equivalent to a fixed point problem

Let LaTeX: \mathcal K be a closed convex cone in the Hilbert space LaTeX: (\mathbb H,\langle\cdot,\cdot\rangle) and LaTeX: f:\mathbb H\to\mathbb H a mapping. Then, the nonlinear complementarity problem LaTeX: NCP(f,\mathcal K) is equivalent to the fixed point problem LaTeX: Fix(P_{\mathcal K}\circ(I-f)), where LaTeX: I:\mathbb H\to\mathbb H is the identity mapping defined by LaTeX: I(x)=x\, and LaTeX: P_{\mathcal K} is the projection onto LaTeX: \mathcal K.

Proof

For all LaTeX: x\in\mathbb H denote LaTeX: z=x-f(x)\, and LaTeX: y=-f(x).\, Then, LaTeX: z=x+y.\,

Suppose that LaTeX: x\, is a solution of LaTeX: NCP(f,\mathcal K). Then, LaTeX: z=x+y,\, with LaTeX: x\in\mathcal K, LaTeX: y\in\mathcal K^\circ and LaTeX: \langle x,y\rangle=0. Hence, by using Moreau's theorem, we get LaTeX: x=P_{\mathcal K}z. Therefore, LaTeX: x\, is a solution of LaTeX: Fix(P_{\mathcal K}\circ(I-f)).

Conversely, suppose that LaTeX: x\, is a solution of LaTeX: Fix(P_{\mathcal K}\circ(I-f)). Then, LaTeX: x\in\mathcal K and by using Moreau's theorem

LaTeX: z=P_{\mathcal K}(z)+P_{\mathcal K^\circ}(z)=x+P_{\mathcal K^\circ}(z).

Hence, LaTeX: P_{\mathcal K^\circ}(z)=z-x=y,. Thus, LaTeX: y\in\mathcal K^\circ. Moreau's theorem also implies that LaTeX: \langle x,y\rangle=0. In conclusion, LaTeX: x\in\mathcal K, LaTeX: f(x)=-y\in\mathcal K^* and LaTeX: \langle x,f(x)\rangle=0. Therefore, LaTeX: x\, is a solution of LaTeX: NCP(f,\mathcal K).

An alternative proof without Moreau's theorem

Variational inequalities

Let LaTeX: \mathcal C be a closed convex set in the Hilbert space LaTeX: (\mathbb H,\langle\cdot,\cdot\rangle) and LaTeX: f:\mathbb H\to\mathbb H a mapping. The variational inequality defined by LaTeX: \mathcal C and LaTeX: f\, is the problem

LaTeX: 
VI(f,\mathcal C):\left\{
\begin{array}{l} 
Find\,\,\,x\in\mathcal C\,\,\,such\,\,\,that\\ 
\langle y-x,f(x)\rangle\geq 0,\,\,\,for\,\,\,all\,\,\,y\in\mathcal C.
\end{array}
\right.

Every variational inequality is equivalent to a fixed point problem

Let LaTeX: \mathcal C be a closed convex set in the Hilbert space LaTeX: (\mathbb H,\langle\cdot,\cdot\rangle) and LaTeX: f:\mathbb H\to\mathbb H a mapping. Then the variational inequality LaTeX: VI(f,\mathcal C) is equivalent to the fixed point problem LaTeX: Fix(P_{\mathcal C}\circ(I-f)).

Proof

LaTeX: x\, is a solution of LaTeX: Fix(P_{\mathcal C}\circ(I-f)) if and only if LaTeX: x=P_{\mathcal C}(x-f(x)). By using the characterization of the projection the latter equation is equivalent to

LaTeX: \langle x-f(x)-x,y-x\rangle\leq0,

for all LaTeX: y\in\mathcal C. But this holds if and only if LaTeX: x\, is a solution of LaTeX: VI(f,\mathcal C).

Remark

The next section shows that the equivalence of variational inequalities and fixed point problems is much stronger than the equivalence of nonlinear complementarity problems and fixed point problems, because each nonlinear complementarity problem is a variational inequality defined on a closed convex cone.

Every variational inequality defined on a closed convex cone is equivalent to a complementarity problem

Let LaTeX: \mathcal K be a closed convex cone in the Hilbert space LaTeX: (\mathbb H,\langle\cdot,\cdot\rangle) and LaTeX: f:\mathbb H\to\mathbb H a mapping. Then, the nonlinear complementarity problem LaTeX: NCP(f,\mathcal K) is equivalent to the variational inequality LaTeX: VI(f,\mathcal K).

Proof

Suppose that LaTeX: x\, is a solution of LaTeX: NCP(f,\mathcal K). Then, LaTeX: x\in\mathcal K, LaTeX: f(x)\in\mathcal K^* and LaTeX: \langle x,f(x)\rangle=0. Hence,

LaTeX: \langle y-x,f(x)\rangle\geq 0,

for all LaTeX: y\in\mathcal K. Therefore, LaTeX: x\, is a solution of LaTeX: VI(f,\mathcal K).

Conversely, suppose that LaTeX: x\, is a solution of LaTeX: VI(f,\mathcal K). Then, LaTeX: x\in\mathcal K and

LaTeX: \langle y-x,f(x)\rangle\geq 0,

for all LaTeX: y\in\mathcal K. Particularly, taking LaTeX: y=0\, and LaTeX: y=2x\,, respectively, we get LaTeX: \langle x,f(x)\rangle=0. Thus, LaTeX: \langle y,f(x)\rangle\geq 0, for all LaTeX: y\in\mathcal K, or equivalently LaTeX: f(x)\in\mathcal K^*. In conclusion, LaTeX: x\in\mathcal K, LaTeX: f(x)\in\mathcal K^* and LaTeX: \langle x,f(x)\rangle=0. Therefore, LaTeX: x\, is a solution of LaTeX: NCP(f,\mathcal K).

Concluding the alternative proof

Since LaTeX: \mathcal K is a closed convex cone, the nonlinear complementarity problem LaTeX: NCP(f,\mathcal K) is equivalent to the variational inequality LaTeX: VI(f,\mathcal K), which is equivalent to the fixed point problem LaTeX: Fix(P_{\mathcal K}\circ(I-f)).

Implicit complementarity problems

Let LaTeX: \mathcal K be a closed convex cone in the Hilbert space LaTeX: (\mathbb H,\langle\cdot,\cdot\rangle) and LaTeX: f,g:\mathbb H\to\mathbb H two mappings. Recall that the dual cone of LaTeX: \mathcal K is the closed convex cone LaTeX: \mathcal K^*=-\mathcal K^\circ, where LaTeX: \mathcal K^\circ is the polar of LaTeX: \mathcal K. The implicit complementarity problem defined by LaTeX: \mathcal K and the ordered pair of mappings LaTeX: (f,g)\, is the problem

LaTeX: 
ICP(f,g,\mathcal K):\left\{
\begin{array}{l} 
	Find\,\,\,u\in\mathbb H\,\,\,such\,\,\,that\\ 
	g(u)\in\mathcal K,\,\,\,f(u)\in K^*\,\,\,and\,\,\,\langle g(u),f(u)\rangle=0.
\end{array}
\right.

Every implicit complementarity problem is equivalent to a fixed point problem

Let LaTeX: \mathcal K be a closed convex cone in the Hilbert space LaTeX: (\mathbb H,\langle\cdot,\cdot\rangle) and LaTeX: f,g:\mathbb H\to\mathbb H two mappings. Then, the implicit complementarity problem LaTeX: ICP(f,g,\mathcal K) is equivalent to the fixed point problem LaTeX: Fix(I-g+P_{\mathcal K}\circ(g-f)), where LaTeX: I:\mathbb H\to\mathbb H is the identity mapping defined by LaTeX: I(x)=x.\,

Proof

For all LaTeX: u\in\mathbb H denote LaTeX: z=g(u)-f(u),\, LaTeX: x=g(u)\, and LaTeX: y=-f(u).\, Then, LaTeX: z=x+y.\,

Suppose that LaTeX: u\, is a solution of LaTeX: ICP(f,g,\mathcal K). Then, LaTeX: z=x+y,\, with LaTeX: x\in\mathcal K, LaTeX: y\in\mathcal K^\circ and LaTeX: \langle x,y\rangle=0. Hence, by using Moreau's theorem, we get LaTeX: x=P_{\mathcal K}z. Therefore, LaTeX: u\, is a solution of LaTeX: Fix(I-g+P_{\mathcal K}\circ(g-f)).

Conversely, suppose that LaTeX: u\, is a solution of LaTeX: Fix(I-g+P_{\mathcal K}\circ(g-f)). Then, LaTeX: x\in\mathcal K and by using Moreau's theorem

LaTeX: z=P_{\mathcal K}(z)+P_{\mathcal K^\circ}(z)=x+P_{\mathcal K^\circ}(z).

Hence, LaTeX: P_{\mathcal K^\circ}(z)=z-x=y,. Thus, LaTeX: y\in\mathcal K^\circ. Moreau's theorem also implies that LaTeX: \langle x,y\rangle=0. In conclusion, LaTeX: g(u)=x\in\mathcal K, LaTeX: f(u)=-y\in\mathcal K^* and LaTeX: \langle x,f(x)\rangle=0. Therefore, LaTeX: u\, is a solution of LaTeX: ICP(f,g,\mathcal K).

Remark

In particular if LaTeX: g=I, we obtain the result Every nonlinear complementarity problem is equivalent to a fixed point problem, but the more general result Every implicit complementarity problem is equivalent to a fixed point problem has no known connection with variational inequalities. Therefore, using Moreau's theorem is essential for proving the latter result.

Personal tools